Pengaruh Konsentrasi Glutaraldehid Pada Komposisi Membran Elektroda Biosensor Pestisida Karbamat - Mashuni Mashuni; Muhammad Syahrul; Ahyar Ahmad; Abdul Wahid Wahab (Hasanuddin University, 2010)
In recent years carbamic pesticides, which show low environmental persistence but a high acute toxicity. Their presence in environmental and food poses a potential hazard to human health and there is a growing interest in their rapid and accurate determination for food safety and environmental monitoring. The aim of this research is to design biosensor for analyzing carbamate pesticides residue in sample show with composite variable concentrate glutaraldehyde (GA) in electrode membrane. Enzim acetylcholinesterase (AChE) was co-immobilised with choline oxidase (ChO) onto a platinum (Pt) surface using a solution of 10% cellulose acetate and 15%, 20%, 25% glutaraldehyde. Result of this research show that glutaraldehyde 15% the detection limit is 10-7,8 M for glutaraldehyde 20% the detection limit is 10-8,4 M and glutaraldehyde 25% the detection limit is 10-8,7 M. This a results is approximately equal to 0,0022 ppm or 2,2 ppb – 0,0002 ppm or 0,2 ppb, which means that this biosensor is sensitive for determining carbamates pesticides residue where its detection limit is comparable to to the detection limit of conventional instrument such as Gas Chromatography (GC) and High Pressure Liquid Chromatography (HPLC), i.e. respectively 1,5 ppb and 2,0 ppb. The proposed electrochemical pesticide sensitivity test exhibited high sensitivity, desirable accuracy, low cost and simplified procedure.Keywords: Biosensors, glutaraldehyde, cellulose acetate, immobilised, carbamate Biosensors, glutaraldehyde, cellulose acetate, immobilised, carbamate pesticides